Communicating Health and Nutrition Information After the Death of Expertise. Issue 6 (November 2017) - Rowe, Sylvia B.; Alexander, Nick
Abstract : This article reframes an issue first visited a decade ago in a Nutrition Today article about the decline in influence of the "gatekeepers" of scientific information. In the current "post-truth" era, characterized by an underskeptical view of "facts, " some observers have expressed fears that public trust in scientific and other expertise is on the decline or, worse, has evaporated altogether. With the ascendancy of Web-based analysis of everything from climate science to nutrition and food safety, these observers fear that actual scientists working in food and health no longer have influence in public discussions. The issue impacts not only scientific issues, but literally everything from pop culture, including music, books, movies, and the like, to highly technical fields such as health insurance and finance: all are subject to this "expertise devaluation" phenomenon. This article explores the arguments and reviews the communication landscape, offering insights into a new disciplined framework for how society, and specifically nutritionists, might extricate themselves from the current minimal trust environment.